2010
DOI: 10.1098/rsta.2010.0203
|View full text |Cite
|
Sign up to set email alerts
|

The rose petal effect and the modes of superhydrophobicity

Abstract: The wetting of rough surfaces remains a subject of active investigation by scientists. The contact angle (CA) is a traditional parameter used to characterize the hydrophobicity/philicity of a solid surface. However, it was found recently that high CAs can coexist with strong adhesion between water and a solid surface in the case of the so-called 'rose petal effect'. Several additional parameters have been proposed to characterize the interaction of water with a rough solid surface, including the CA hysteresis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
374
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(396 citation statements)
references
References 33 publications
14
374
0
3
Order By: Relevance
“…It has been demonstrated that multiple roughness scales enhance surface wettability when the basic geometry of the roughness is the same and the presence of a nanostructure on the surface is responsible for the high water contact angle. 57,58 So the variations in wettability can be attributed to differences in the nanofeatures superimposed on the surface of the micro-sized structures. The top surface of the micro-sized protrusions for pure superhydrophilic TiO 2 coating (S-H-0) is mainly composed of smooth well-molten TiO 2 splats with diameter 200 nm to 5 mm, and pores constructed by these splats (Fig.…”
Section: Wettability Propertiesmentioning
confidence: 99%
“…It has been demonstrated that multiple roughness scales enhance surface wettability when the basic geometry of the roughness is the same and the presence of a nanostructure on the surface is responsible for the high water contact angle. 57,58 So the variations in wettability can be attributed to differences in the nanofeatures superimposed on the surface of the micro-sized structures. The top surface of the micro-sized protrusions for pure superhydrophilic TiO 2 coating (S-H-0) is mainly composed of smooth well-molten TiO 2 splats with diameter 200 nm to 5 mm, and pores constructed by these splats (Fig.…”
Section: Wettability Propertiesmentioning
confidence: 99%
“…Bhushan and Nosonovsky demonstrated that wetting of hierarchical reliefs may be of a complicated nature, resulting in the "rose petal effect", as shown in Fig. 20 [77]. Various wetting modes are possible for hierarchical reliefs: it is possible that a liquid fills the larger grooves, whereas small-scaled grooves are not wetted and trap air as shown in Fig.…”
Section: The Rose Petal Effectmentioning
confidence: 99%
“…According to Ref. 77 the larger structure controls the contact angle hysteresis, whereas the smaller (usually nanometric) scale is responsible for high contact angles [77,78]. Thus, the relief depicted in Fig.…”
Section: The Rose Petal Effectmentioning
confidence: 99%
“…It was suggested that hierarchical roughness is a critical element for stabilizing a composite interface. [7][8][9] We show that the factors affected on stability of superhydrophobicity can be resolved by making hierarchical multiple air-traps, maintaining static and dynamic superhydrophobicity over one year. The MTS consists of three trapping sites for air, and those are nanocone array, micropore array, and nanogrooves.…”
mentioning
confidence: 99%
“…However, the composite interface is usually quite unstable towards external stimuli, consequently leading to loss of hydrophobocity. [5][6][7][8][9] Thus, stabilizing the composite interface is crucial to maintain long-term stability of roughness induced hydrophobicity, which is closely related to the ability of air-trapping in a rough surface. In addition, to enhance anti-reflectance and absorption in a broad range of the sun spectrum light should be effectively trapped by surface features.…”
mentioning
confidence: 99%